Analisis faktor-faktor yang mempengaruhi pilihan karir mahasiswa farmasi di Universitas Andalas - Pratiwi, Erniza; Putra, Deddi Prima; Syahrul, Laura (Universitas Ahmad Dahlan, 2017)
Scope of pharmacy practices as well as the role of pharmacist have been improving recently. Pharmacists have responsibility for doing the pharmacy practices, including pharmacist it self and also the technicians. According to PP 51 of the year 2009 it was known that pharmaceutical practices have vary of choice of carreer-field. This present study was a descriptive study which was conducted by survey method using stratified random sampling. The respondents of this study were 1st, 2nd, 3rd and 4th grade students from Faculty of Pharmacy, Andalas University. The result showed that, in term of the profile of respondent, it was known that most of the students chose to work at industry of pharmacy of 48.2%, followed by hospital ofÂ 35.3%, University/Research Institute of 4.7%, pharmacy of 3.5%, pharmacy retail of 2.4% and others career-field (such as BPOM, civil servant at ministry of health and enterpreneur) up to 5.9%. Based on descriptive analysis, it was described that field of work was the most important criteria of affecting factors for pharmacy student in choosing their future career. The others important criterias those also afforded as the affecting factors were geographis, payment/income, flexibility of work-schedule, possibility of career-development and benefit, successively. As for result of independent sample t-test in term of gender, both of men and women chose same three main affecting factors in choosing career-field (including field of work, geographis as well as payment/income). The different result showed for 4th, 5th and 6th factors.